Protection against experimental pseudomembranous colitis in gnotobiotic mice by use of monoclonal antibodies against Clostridium difficile toxin A. - Corthier, G (1991)
The pathogenicity of Clostridium difficile is due to the production of two toxins (toxins A and B). We prepared monoclonal antibodies against toxin A and determined whether axenic mice passively immunized with the monoclonal antibodies were protected against C. difficile disease. The mice were kept in an isolator and were given ascites fluid intravenously prior to challenge with a toxinogenic strain of C. difficile. Control mice and mice receiving ascites fluid devoid of toxin antibody died within 2 days and had high levels of toxins A and B in their feces. Mice that received ascites fluid containing high amounts of toxin A monoclonal antibodies directed against the repeating units of the toxin survived. In protected mice, toxin B levels were similar to those in dying mice, but toxin A levels were greatly reduced. These data show that passive immunity induced by monoclonal antibodies against toxin A was effective against pseudomembranous cecitis.